Effect of Lipophilic Bismuth Nanoparticles on Erythrocytes - Hernández Delgadillo, René; Badireddy, Appala Raju; Zaragoza Magaña, Valentín; Sánchez Nájera, Rosa Isela; Chellam, Shankararaman; Cabral Romero, Claudio (2015)
Lipophilic bismuth dimercaptopropanol nanoparticles (BisBAL NPs) have a very important antimicrobial activity; however their effect on human cells or tissues has not been completely studied. Undesirable effects of bismuth include anemia which could result from suicidal erythrocyte death or eryptosis. The objective of this research was to determine the effect of bismuth dimercaptopropanol nanoparticles on blood cells. The nanoparticles are composed of 53 nm crystallites on average and have a spherical structure, agglomerating into clusters of small nanoparticles. Based on cell viability assays and optical microscopy, cytotoxicity on erythrocytes was observed after growing with 500 and 1000